In Defense of Capitalism: Modern Slavery Would Be Much Worse Without It. Issue 3 (March 2023) - Arora, Punit; Stephen, Sarah Lilian
Some scholars blame capitalism for the prevalence of modern slavery. However, data reveal that it is wrong to blame capitalism for a problem that long preceded it and would likely be much worse without it. We explain why this is the case.